UMPSA acknowledges the success of outstanding academic staff and graduates - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2024)
KUANTAN, 14 February 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) honoured the exceptional achievements of its academic staff and postgraduate students at the UMPSA Postgraduate Appreciation Ceremony 2023 held today at the Swiss-Belhotel Kuantan.